International Trade in General Oligopolistic Equilibrium - J. Peter Neary (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper presents a new model of oligopoly in general equilibrium and explores its implications for positive and normative aspects of international trade. Assuming “continuum-Pollak” preferences, the model allows for consistent aggregation over a continuum of sectors, in each of which a small number of home and foreign firms engage in Cournot competition. I show how competitive advantage interacts with comparative advantage to determine resource allocation, and, specializing to continuum-quadratic preferences, I explore the model's implications for the gains from trade, for the distribution of income between wages and profits, and for production and trade patterns in a two-country world.
Keywords: F10; F12; 330; “Continuum-Pollak” preferences; Continuum-quadratic preferences; GOLE (General Oligopolistic Equilibrium); market integration; trade and income distribution